2014
DOI: 10.2337/db13-0636
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Hyperactivity Due to Ventromedial Hypothalamic Lesions Increases Adiponectin Production and Release

Abstract: In obese humans and animals, adiponectin production and release in adipose tissue are downregulated by feedback inhibition, resulting in decreased serum adiponectin. We investigated adiponectin production and release in ventromedial hypothalamic (VMH)-lesioned animals. VMH-lesioned mice showed significant increases in food intake and body weight gain, with hyperinsulinemia and hyperleptinemia at 1 and 4 weeks after VMH-lesioning. Serum adiponectin was elevated in VMH-lesioned mice at 1 and 4 weeks, despite adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 47 publications
(60 reference statements)
0
7
0
Order By: Relevance
“…Parasympathetic activity plays a key role in blood pressure regulation, adiposity and metabolic activity.Acutely, olanzapine induces a potent increase of parasympathetic tone translated into a decrease in blood pressure and heart rate in rats and postural hypotension in humans. Parasympathetic hyperactivation may contribute to the development of metabolic syndrome, obesity or other SGA‐induced adverse metabolic effects. Our anatomical analysis shows that olanzapine activates the parasympathetic branch of the ANS, with melatonin vastly mitigating this effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasympathetic activity plays a key role in blood pressure regulation, adiposity and metabolic activity.Acutely, olanzapine induces a potent increase of parasympathetic tone translated into a decrease in blood pressure and heart rate in rats and postural hypotension in humans. Parasympathetic hyperactivation may contribute to the development of metabolic syndrome, obesity or other SGA‐induced adverse metabolic effects. Our anatomical analysis shows that olanzapine activates the parasympathetic branch of the ANS, with melatonin vastly mitigating this effect.…”
Section: Resultsmentioning
confidence: 99%
“…The biological clock selectively coordinates ANS balance to influence metabolism in different parts of the body, so alteration of this output may over time precipitate problems in metabolism such as the metabolic syndrome. Acute parasympathetic activation induces adiposity and an increase in plasmatic adiponectin. Such effects are also observed with short‐term treatment with olanzapine.…”
Section: Discussionmentioning
confidence: 99%
“…The circulating levels of high‐molecular‐weight adiponectin in healthy humans follow circadian variations that are not driven by the feeding–fasting cycle . This rhythm may be based upon the activity of the autonomic branches since in vitro and in vivo studies have shown that sympathetic/β‐adrenergic stimulation of adipose tissue inhibits the production and secretion of adiponectin , whereas parasympathetic activation increases it . Thus, it is possible that in the course of NAFLD, an enhanced sympathetic and/or decreased parasympathetic input to adipose tissue may result in decreased adiponectin levels, contributing to disease progression.…”
Section: Expressway From Simple Steatosis To Non‐alcoholic Steatohepamentioning
confidence: 99%
“…In the case of VMH lesions, a unique enhancement of parasympathetic vagal nerve activity is produced that is associated with increased insulin, gastric acid secretion, gastric emptying, and gastrointestinal cell proliferation (Hales and Kennedy, 1964 ; Ridley and Brooks, 1965 ; Frohman and Bernardis, 1968 ; Frohman et al, 1969 ; Han and Frohman, 1970 ; Bernardis and Frohman, 1971 ; Inoue et al, 1977 , 1983 ; Jeanrenaud, 1978 ; Berthoud and Jeanrenaud, 1979 ; Bray and York, 1979 ; Inoue and Bray, 1979 , 1980 ; Sawchenko, 1979 ; Weingarten and Powley, 1980 ; Bray et al, 1981 ; Cox and Powley, 1981a ; Bray, 1984 ; Yoshimatsu et al, 1984 ; Duggan and Booth, 1986 ; Kiba et al, 1992 , 1993 , 1996 ; Kintaka et al, 2009 ; Suzuki et al, 2014 ), which in the case of hyperinsulinemia and gastric hyperacidity is counteracted by SDV (Powley and Opsahl, 1974 ; Inoue and Bray, 1977 ; Berthoud and Jeanrenaud, 1979 ).…”
Section: Introductionmentioning
confidence: 99%